Voices beyond the wall : twelve love poems from the murder capital of the world (Stories Matter Media, 2017)
Rescued from the streets of San Pedro Sula, Honduras, murder capital of the world, orphaned girls find their voices in poetry as they heal traumas of their past and prepare to transition into an uncertain future. --